2016
DOI: 10.1007/s10549-016-4054-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mammographic density between Asian and Caucasian populations: a comparative analysis

Abstract: Our analysis suggests that among post-menopausal women, population differences in mammographic density and risk to breast cancer may be accounted for by height, weight, and parity. Given that pre-menopausal Asian and Caucasian women have similar population risk to breast cancer but different dense volume, development of more appropriate biomarkers of risk in pre-menopausal women is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 37 publications
2
61
1
Order By: Relevance
“…Variations in breast size and tissue composition across different populations may also affect the association between MD and TDLU features differently. Although not always consistent, studies comparing racial differences in MD suggest that Asian women have higher percent MD but smaller absolute dense area/volume and breast size compared to Western women after accounting for well‐known MD determinants such as age and BMI . It is also notable that intact TDLU structures were persistent even in very old women (up to age 79 years) in our study, whereas a high proportion of subjects showed complete involution among younger women (zero TDLU count: 25%; 40–65 years) in the STAMP study .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Variations in breast size and tissue composition across different populations may also affect the association between MD and TDLU features differently. Although not always consistent, studies comparing racial differences in MD suggest that Asian women have higher percent MD but smaller absolute dense area/volume and breast size compared to Western women after accounting for well‐known MD determinants such as age and BMI . It is also notable that intact TDLU structures were persistent even in very old women (up to age 79 years) in our study, whereas a high proportion of subjects showed complete involution among younger women (zero TDLU count: 25%; 40–65 years) in the STAMP study .…”
Section: Discussioncontrasting
confidence: 59%
“…Although not always consistent, studies comparing racial differences in MD suggest that Asian women have higher percent MD but smaller absolute dense area/volume and breast size compared to Western women after accounting for well-known MD determinants such as age and BMI. [21][22][23][24][25][26] It is also notable that intact TDLU structures were persistent even in very old women (up to age 79 years) in our study, whereas a high proportion of subjects showed complete involution among younger women (zero TDLU count: 25%; 40-65 years) in the STAMP study. 4,15 Furthermore, while we found strong correlations of all three TDLU measures (all Spearman's rho>0.63; Supporting Information Table 2), previous studies reported a strong correlation between TDLU size measures (acini count and span) but a weaker correlation of TDLU count with either size measure (all Spearman's rho<0.18).…”
Section: And the Stamp 4 Used Benign Tissues From Women With Bbdsupporting
confidence: 38%
“…VMD measures have produced reasonably strong associations with breast cancer risk when validated against visual assessment and computer-assisted methods (11). As VMD methods are becoming increasingly used in epidemiologic studies of density (12)(13)(14)(15)(16)(17)(18), it becomes important to understand not only how VMD measures are associated to breast cancer risk, but also how they relate to established breast cancer risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Jung Sun Lee 1 *, Minkyung Oh 2 breast density on mammography and breast cancer risk for Asian women, regardless of menopausal status. However, Rajaram et al, (2017) suggested that premenopausal Asian and Caucasian women are at similar risk of breast cancer regardless of different breast density. Furthermore, several reproductive and lifestyle factors that influence the risk of breast cancer have been consistently associated with breast density (Brisson et al, 1984;Boyd et al, 2005;Sellers et al, 2007;Martin et al, 2008;Martin et al, 2010).…”
Section: Breast Density Of Mammography Is Correlated With Reproductivmentioning
confidence: 99%